Redefining Engagement with Socio-spatially Marginalised Populations: Learning from Ghana's Ministry of Inner City and Zongo Development. (May 2019) - Brady, Colleen; Hooper, Michael
Global interest in enhancing accountability and community participation has led many governments to engage socio-spatially marginalised populations left behind by urban development. This article examines an emergent example of these efforts: Ghana's Ministry of Inner City and Zongo Development (MICZD). The MICZD's objective is to improve the social and infrastructural development of zongos, or 'stranger's quarters', which have historically housed Hausa migrants and are associated with slum-like conditions. The study draws on 38 interviews with government stakeholders, community organisations and local leaders as well as on four focus groups with zongo residents. The results reveal four key findings. First, the MICZD's engagement with zongos is perceived as politically motivated, with this viewed negatively by some and positively by others. Second, the MICZD's timeline is perceived differently depending on who is being asked. Third, respondents differ in their prioritisation of physical versus social improvements, with the MICZD focussing on physical interventions and zongo residents focussing on social and economic development. Finally, different groups have varied visions of success for the MICZD. The article concludes by identifying two paths towards more empowering state–society engagement—more continuous engagement and counterbalancing powers—and proposes how lessons from the MICZD can inform engagement with marginalised populations more broadly.